RANCANG BANGUN APLIKASI MOBILE LEARNING TENSES BAHASA INGGRIS - Putu Bagus Adidyana Anugrah Putra; Nova Noor Kamala Sari; Efrans Christian (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2019)
All that requires a media to understand each other and understand one another. The media is language. Language is a medium for communication so cooperation will be created in various aspects. English is the connecting language used as a medium of communication between countries in the world. But some people find it difficult when learning English. The difficulty experienced is due to a lack of understanding of grammar, one of which includes tenses. Learning media as a means of improving the quality of education is very important in the learning process. The research methodology used is waterfall method as an application development methodology. The first step to do is to analyze the needs of the system made, including library research, data collection, consultation, and design. From this analysis a system design using usecase diagrams, activity diagrams and class diagrams is made as a system design to be made. After the system is designed, the next step is to write the program code. At writing the programming language program code used is java, android studio and genymotion as an emulator. Blacbox test results show the software can find out the functions that are not correct, interface errors, performance errors and functionally produce the expected results.